Associations of staple food consumption and types of cooking oil with waist circumference and body mass index in older Chinese men and women: a panel analysis. Issue 2 (12th October 2020) - Lee, Yen-Han; Chang, Yen-Chang; Ang, Ting Fang Alvin; Chiang, Timothy; Shelley, Mack; Liu, Ching-Ti
Abstract: Background: The dietary landscape has changed rapidly in China in the past few decades. This research investigates the associations of older adults' choices and consumption of staple foods and cooking oils with obesity-related measurements. Methods: Panel data were extracted from the Chinese Longitudinal Health Longevity Survey from 3253 older participants with 6506 observations. Ordinary least squares and ordered logistic regression models were estimated with the outcomes of obesity determined by waist circumference (WC) and body mass index (BMI), respectively. Results: Older men who consumed wheat had wider WCs (β=2.84 [95% confidence interval CI 1.55 to 4.13], p<0.01) and higher BMIs (adjusted odds ratio 1.74 [95% CI 1.40 to 2.17], p<0.01) than those who preferred rice. Female participants who used animal-based cooking oil had lower WCs and BMIs than their counterparts who consumed vegetable-based cooking oil. Increased consumption of staple foods was associated with increased rates of obesity in both sexes. Conclusion: Dieticians and nutritionists should design appropriate dietary plans to help reduce obesity and chronic diseases among older Chinese adults. Further clinical trials are needed to continue investigating this topic.